Secretion of Salmonella Pathogenicity Island 1-Encoded Type III Secretion System Effectors by Outer Membrane Vesicles in Salmonella enterica Serovar Typhimurium - Kim, Seul I; Kim, Seongok; Kim, Eunsuk; Hwang, Seo Yeon; Yoon, Hyunjin (Frontiers in Microbiology, 2018)
Outer membrane vesicles (OMVs) are spherical membranous structures released by Gram-negative bacteria. Several bacterial pathogens utilize OMVs as vehicles for the delivery of virulence factors into host cells. Results of our previous study on proteomic analysis revealed that OMVs isolated from Salmonella enterica serovar Typhimurium had virulence effectors that are known to be translocated by Salmonella pathogenicity island 1 (SPI-1)-encoded type III secretion system (T3SS1) into the host cell. In the present study, immunoblot analysis confirmed the secretion of the six T3SS1 effector proteins, namely SipB and SipC (translocators of T3SS1), and SipA, SopA, SopB, and SopE2 (effectors translocated by T3SS1), by OMVs. Results of proteinase K treatment revealed the localization of these T3SS1 effector proteins on the outer surface of OMVs. SipC and SopE2 were secreted by OMVs independent of the three secretion systems T3SS1, T3SS2, and flagella, signifying OMVs to be an alternative delivery system to T3SSs. T3SS1 effectors SipA, SipC, and SopE2 were internalized into the cytoplasm of the host cell by OMVs independent of cellular Salmonella-host cell contact. In epithelial cells, addition of OMVs harboring T3SS1 effectors stimulated the production of F-actin, thereby complementing the attenuated invasion of ΔsopE2 into host cells. These results suggest that S. Typhimurium might exploit OMVs as a long-distance vehicle to deliver T3SS1 effectors into the cytoplasm of the host cell independent of bacteria-host cell interaction.